Supervisor Optimization in Improving the Quality of Education - Setyaningsih, Rini; Windra, Nadilla; Dinata, Yuriyan; Irawati, Irawati (Journal of Asian Islamic Educational Management (JAIEM), 2023)
This study aims to describe the efforts of supervisors of the Tanah Datar Regency education office at Batusangkar Progressive Vocational School in optimizing the supervisory function to improve the quality of education. The type of research is qualitative with a case study approach carried out online through google meet—research data obtained utilizing in-depth interviews. The data shows that the optimization of the supervision function follows the purpose of supervision, which is carried out regularly and continuously. The method used to optimize the supervisory function is academic and managerial supervision. All problems can be solved independently at the time of supervision. Follow-up for other problems is to provide alternatives in creative supervision, modeling, and OKE PDKT techniques. This study offers a supervisor to better understand and improve his quality as a school supervisor to realize a highly competitive education.